Identification of L1 ORF2p sequence important to retrotransposition using Bipartile Alu retrotransposition (BAR) - Christian, Claiborne M. (Nucleic Acids Res, 2016)
Long Interspersed Element 1 (LINE-1 or L1) is capable of causing genomic instability through the activity of the L1 ORF2 protein (ORF2p). This protein contains endonuclease (EN) and reverse transcriptase (RT) domains that are necessary for the retrotransposition of L1 and the Short Interspersed Element (SINE) Alu. The functional importance of approximately 50% of the ORF2p molecule remains unknown, but some of these sequences could play a role in retrotransposition, or be necessary for the enzymatic activities of the EN and/or RT domains. Conventional approaches using the full-length, contiguous ORF2p make it difficult to study the involvement of these unannotated sequences in the function of L1 ORF2p. Our lab has developed a Bipartile Alu Retrotransposition (BAR) assay that relies on separate truncated ORF2p fragments: an EN-containing and an RT-containing fragment. We validated the utility of this method for studying the ORF2p function in retrotransposition by assessing the effect of expression levels and previously characterized mutations on BAR. Using BAR, we identified two pairs of amino acids important for retrotransposition, an FF and a WD. The WD appears to play a role in cDNA synthesis by the ORF2p molecule, despite being outside the canonical RT domain.